The use of cultural heritage in economic and human development: a comparison of built heritage projects in Morocco and British Columbia - Richtscheid, Kevin Graham (2011)
Recent decades have found those in the development field seeking alternatives to resource-extraction based approaches to development. The use of Cultural Heritage, and specifically built heritage projects, has become one such approach that offers more sustainable and culturally-sensitive alternatives. A few Cultural Heritage projects have been ongoing for decades now, and offer insights into how these sorts of initiatives can be approached, and what can be learned from them and applied to similar situations in other parts of the world. The old medina of Fez in Morocco is one such well-established project that offers an example of some of the potential, as well as some of the pitfalls, of this endeavour. This project seeks to evaluate these lessons in the light of a few newer Cultural Heritage projects that have been established by First Nations groups in British Columbia, and by comparing them to the medina of Fez. The potential of this approach to development is evaluated in the light of the successes and challenges that these projects face.